Socioeconomic level and the parents' perception of the impact of oral diseases on their children's quality of life - Belila, Naiana de Melo [UNESP]; Martins, Ronald Jefferson [UNESP]; Saliba Garbin, Cléa Adas [UNESP]; Borghi, Wanilda Maria Meire Costa [UNESP] (Universidade Estadual de Campinas, 2016)
Aim: To analyze how parents of different socioeconomic levels perceive the impact of oral diseases on their children's quality of life. Methods: All parents or guardians of students aged 11 to 14 years old, regularly enrolled in fundamental schooling at public schools of two towns in the northwestern region of the State of São Paulo, Brazil, were enrolled in the study. The questionnaire of Socioeconomic Assessment Tool was used to classify the families with regards to socioeconomic class and the Parental-Caregiver Perceptions Questionnaire (P-CPQ) was used to verify the parents' perception of the impact of oral diseases on their children's quality of life. Results: 172 (41.8%) individuals answered the survey. Among them, most belonged to the Upper Low Class (61%). 21.5% of the individuals answered that they considered their children's oral health regular or bad and 71.5% answered that their child's general well-being was not or was little affected by the condition of his/her teeth, lips, jaws or mouth. There was an association between the quality of life sub-scales, especially oral symptoms, with all socioeconomic classes. Conclusions: There is a relationship between parents' socioeconomic class and the perception of the impact of oral disease on their children's quality of life.
Keywords: Oral Health; Quality of Life; Social Class